2014
DOI: 10.1371/journal.pone.0090016
|View full text |Cite
|
Sign up to set email alerts
|

CB1 Blockade Potentiates Down-Regulation of Lipogenic Gene Expression in Perirenal Adipose Tissue in High Carbohydrate Diet-Induced Obesity

Abstract: De novo lipogenesis and hypercaloric diets are thought to contribute to increased fat mass, particularly in abdominal fat depots. CB1 is highly expressed in adipose tissue, and CB1-mediated signalling is associated with stimulation of lipogenesis and diet-induced obesity, though its contribution to increasing fat deposition in adipose tissue is controversial. Lipogenesis is regulated by transcription factors such as liver X receptor (LXR), sterol-response element binding protein (SREBP) and carbohydrate-respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
(82 reference statements)
4
12
0
Order By: Relevance
“…In contrast, PC females with higher perigonadal adiposity but not perirenal adiposity, exhibited greater gene expression of Cnr1 in PAT, when compared to CC females. These results are in agreement to previous reports after chronic exposure to high-carbohydrate diets [86]. Curiously, this increment was not accompanied by other alterations in fatty acid metabolism genes and leptinemia, which suggests an isolated effect.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, PC females with higher perigonadal adiposity but not perirenal adiposity, exhibited greater gene expression of Cnr1 in PAT, when compared to CC females. These results are in agreement to previous reports after chronic exposure to high-carbohydrate diets [86]. Curiously, this increment was not accompanied by other alterations in fatty acid metabolism genes and leptinemia, which suggests an isolated effect.…”
Section: Discussionsupporting
confidence: 93%
“…In the adipose tissue, activation of CB1 receptors increase lipoprotein lipase (LPL), an enzyme required for fatty acid uptake and storage, in a dose dependent manner [ 31 ] which, together with increased activity of fatty acid synthase (FAS) and inhibition of monophosphate-activated protein kinase (AMPK), results in increased lipogenesis and decreased lipolysis and fatty acid oxidation [ 32 ] . The demonstration that CB1 blockade potentiates downregulation of lipogenic gene expression in perirenal adipose tissue in high carbohydrate diet-induced obesity corroborates these fi ndings [ 33 ] . In the liver, CB1 receptors upregulate the lipogenic transcription factor sterol regulatory element binding transcription factor 1 (SREBF1), thus enhancing the expression of acetyl-Coenzyme A carboxylase-α (ACC1) and FAS, resulting in increased lipogenesis [ 34 ] .…”
supporting
confidence: 72%
“…Second, studies in mice, rats, and humans revealed downregulation of de novo lipogenesis in adipose tissue in obesity [35–37] , which has been suggested as an adaptive process to limit an ongoing increase of fat mass [37] . Cellular ATP demand for lipogenic enzyme activity, and the resulting requirement for mitochondrial OXPHOS activity for this process, would therefore be reduced.…”
Section: Discussionmentioning
confidence: 99%